The Influence of Location on Purchasing Decisions at the Plastic King Shop in Mancang Village, Samudera Sub-District, Northern Aceh District - Mahnidar, Mahnidar; Ritonga, Nursakinah; Sufi, Sufi; Maisyura, Maisyura; Ameliany, Nanda (LPPM UIKA Bogor, 2024)
This study aims to determine the effect of location on purchasing decisions at Raja Plastik stores in Mancang Village, Samudera District, North Aceh Regency. This study uses descriptive quantitative research methods with 97 respondents as the research sample obtained from the lemesshow formula. The data analysis method used in this research is simple regression analysis with the help of the SPSS 20.0 program. Data collection techniques using a questionnaire. The results showed that through a t-test with a significant value of 5.053 at the 5% error rate, it was concluded that location had a positive and significant effect on purchasing decisions at Raja Plastik stores in Samudera District, North Aceh Regency. Based on the results of hypothesis testing, it can be concluded that Ha is accepted. This study focuses on specific aspects of the location of the Raja Plastik store such as access, visibility, traffic and parking. This study also examines the impact of the store's proximity to public transportation centers and its location near shopping areas and dense residential areas.